Cadastro técnico multifinalitário da cidade de Camaçari (BA): uma proposta de sistematização para auxiliar o planejamento urbano - Santos, Flávio Gomes (2023)
Over the years, urban management tends to improve with appropriate tools and instruments that understand the socioeconomic dynamics that materialize in space. In this context, the present work aims to propose, through the quantitative method that analyzes the set of geometric data, the systematization of the Multipurpose Technical Register (CTM) in order to collaborate with the administrations of the municipality of Camaçari in territorial planning. For that, we chose to also carry out documentary research in order to carry out a general analysis of the planning and, consequently, of the plans implemented in Camaçari, in addition, we listed the historical process of the cadastre from its first purposes presented on the world stage to its institutionalization in the Brazil, through Ministerial Ordinance No. 511/2009. In this regard, the work also makes an analysis of the past and present of Camaçari, which despite being a city that has a registry, still needs to make adjustments that meet the determinations of the Ordinance, because the tool is very important in the municipal administrative system, collaborating with urban planning, so that the city has a better organization of space and optimization of the resources that will be applied, so that the population has quality of life. Conceived as a prognosis for the Municipality, the final objective of this work is to assemble and present online the structure of a cadastral database in a GIS environment, through free software, so that the City Hall can incorporate it into the system already used with periodic updates and so that it can give due continuity in the adaptations so that it becomes effective as a CTM, and that in this way it can help the municipality in the operational actions of organization of the urban space and future planning.